IMPLIKASI TINDAK PIDANADI LUAR KUHP DALAM HUKUM ACARA PIDANA (Studi Kasus Taraf Sinkronisasi) - Sulistyanta Sulistyanta (Jurnal Dinamika Hukum, 2013)
Settings outside the Criminal Code offense of criminal procedural law contained (special) on the other hand there is the Criminal Procedure Code (general). Criminal law plays an important role in an integrated criminal justice system. Aspects of the substance in the criminal justice system should be aligned, harmonious and synchronous (vertical or horizontal), do not overlap (overlapping). This study contradicts the implications of the regulation of offenses outside the Penal Code raises a variety of criminal law and a matter of consistency in its application. The approach used is normative-legal and case studies. Secondary data to primary data. Data were collected by the research literature. Data were analyzed qualitatively descriptive. Research purposes to detect the level of synchronization rules. The results: there are many circulars issued by sub justice system, police, prosecutors, and judicial. In some ways inconsistent implementation such, the case KAI vs. PERADI in Kupang and Kupang District Court pre-trial ruling.Key words  : special crimes, the synchronization of criminal procedure and the criminal justice system.